The closure of crossing points at Finland’s eastern border and the right to asylum under EU law - Anttonen, Maria (My University, 2024)
The subject of this thesis is the closure of border crossing points at Finland's eastern border and the right to asylum under EU law. It uses a case study approach, assessing Finland's measures in the light of EU refugee law. The closure of Finland's eastern border crossing points and its implications for the right to asylum under EU law is an issue that involves various legal, political and humanitarian considerations. This thesis examines the EU legal framework on the asylum process, Finland's border closure measures on the eastern border from November 2023 onwards and their impact on the right to seek asylum under EU law. It examines the circumstances in which EU law allows derogations from its asylum obligations and the possible impact of hybrid influencing and instrumentalized migration on these obligations. The study analyzes relevant EU legislation, case law and policy documents to understand the legal basis for border closure measures and their relationship with EU law. It also examines the broader context of instrumentalized migration and hybrid warfare. At the end of the thesis, conclusions are drawn on how border closure measures conflict with the rights of asylum seekers under EU law. The thesis also briefly discusses the new EU immigration legislation, namely the Pact on Asylum and Migration.

Tämän opinnäytetyön aiheena on rajanylityspaikkojen sulkeminen Suomen itärajalla ja EU:n lainsäädännön mukainen oikeus turvapaikkaan. Siinä käytetään tapaustutkimuslähestymistapaa, jossa arvioidaan Suomen toimenpiteitä EU:n pakolaisoikeuden valossa. Suomen itäisten rajanylityspaikkojen sulkeminen ja sen vaikutukset EU:n lainsäädännön mukaiseen turvapaikkaoikeuteen liittyy useita oikeudellisia, poliittisia ja humanitaarisia näkökohtia. Tässä tutkielmassa tarkastellaan turvapaikkaprosessia koskevaa EU:n oikeudellista kehystä, Suomen rajasulkutoimia itärajalla marraskuusta 2023 alkaen ja niiden vaikutuksia EU-oikeuden mukaiseen turvapaikkaoikeuteen. Siinä tarkastellaan, missä olosuhteissa EU:n oikeus sallii poikkeuksia turvapaikkavelvoitteista, sekä hybridivaikuttamisen ja välineellistetyn maahanmuuton mahdollisia vaikutuksia näihin velvoitteisiin. Tutkimuksessa analysoidaan asiaankuuluvaa EU:n lainsäädäntöä, oikeuskäytäntöä ja poliittisia asiakirjoja, jotta voidaan ymmärtää rajojen sulkemistoimenpiteiden oikeusperusta ja niiden suhde EU:n lainsäädäntöön. Siinä tarkastellaan myös välineellistetyn maahanmuuton ja hybridisodankäynnin laajempaa kontekstia. Tutkielman lopussa tehdään johtopäätökset siitä, miten rajojen sulkemistoimenpiteet ovat ristiriidassa turvapaikanhakijoiden EU:n oikeuden mukaisten oikeuksien kanssa. Tutkielmassa käsitellään myös lyhyesti EU:n uutta maahanmuuttolainsäädäntöä eli turvapaikka- ja maahanmuuttosopimusta.
Keywords: EU law, refugee law, right to international protection, instrumentalized migration, hybrid warfare, closure of the eastern land border